Determination of Property Constant of Lead Complexes with Dibromo-o-carboxy-chlorophosphonazo and Dbromo-p-p’-dimethylsulfonazo - Gao, Hong-Wen; Li, Mei; Ye, Qing-Song (Asian Journal of Chemistry, 2010)
Two sensitive reactions between lead(II) and dibromo-o-carboxy- chlorophosphonazo (DBKCPA) at pH 8.5 between lead(II) and dibromo-p-p´-dimethylsulfonazo (DBMSA) at pH 9 were investigated. The β-correction spectrophotometry was applied to the determination of properties of Pb complex solutions instead of the ordinary method. The multi-coordination reaction was observed in Pb-DBKCPA reaction system. Results showed that the complex ratio of Pb(II) to DBKCPA and to DBMSA were equal to 1 : 7 and 1 : 2 respectively. Also, the cumulative stability constant (K) of Pb( (DBKCPA)7 was equal to 3.04 x 1034 and that of Pb(DBMSA)2 1.74 x 1010 and their end-step real absorptivities were as follows: ε630Pb(DBKCPA)7 = 1.10 x 104 L mol–1 cm–1 and ε650Pb(DBMSA)3 = 3.37 x 104 L mol–1 cm–1 respectively.